Legal Loopholes in the Application for Termination of Investigation by Investigators Due to the Absence of Clear Standards in Determining Sufficient Evidence - John Piter Tampubolon; Rineke Sara (Greenation International Journal of Law and Social Sciences, 2025)
This study examines the legal gaps that arise in investigators' requests to terminate investigations based on Article 109 paragraph (2) of the Criminal Procedure Code, which authorizes the filing of an SP3 (Sufficient Evidence Order) due to "insufficient evidence" but does not outline the operational criteria. This lack of clarity in the standard leaves investigators open to subjective interpretation, potentially leading to misuse to terminate investigations without a clear basis, reducing legal certainty and harming victims. The study uses a normative juridical approach with a critical analysis of laws and regulations, legal literature, and investigative practices in Indonesia. The results show that the ambiguity of the term "sufficient evidence" creates a legal loophole that weakens investigator accountability and leads to injustice in the criminal justice system. As a direction for legal reform, it is recommended that there be clear technical guidelines for assessing sufficient evidence, a strict oversight mechanism by prosecutors, and public transparency regarding the basis for terminating investigations, so that the SP3 authority can be exercised objectively, accountably, and in accordance with the principle of legal certainty. This reform is expected to minimize the potential for misuse, increase the integrity of law enforcement, and strengthen the protection of victims' rights.